Middle Neolithic trackway A20 at Kastbjerg Å: High precision dating and archaeological context - Olsen, Jesper; Madsen, Bo; Kanstrup, Marie; Korthauer, Carsten; Klassen, Lutz (Danish Journal of Archaeology, 2024)
In 2015-2017, East Jutland Museum excavated a series of well-preserved prehistoric and early historic trackways at Kastbjerg Å in the Kastbjerg Å river valley (eastern Jutland, Denmark). In this article, we will present the earliest of the in situ preserved structures, the Middle Neolithic trackway A20, and the high-precision dating of this structure. Dendrochronological dating of wood sequences provides very precise ages for archaeological timbers from buildings or structures, such as bridges or ships. This is not possible, however, when the dendrochronological samples lack sapwood, if the wood sequence has too few rings to provide definite placement on the dendrochronological master curve, if the wood sequence falls outside the range of the master curves or if the species of wood is not suitable for dendrochronological analysis. Here, we date a wood sequence of an alder tree from trackway A20 using the radiocarbon wiggle-match method to 2911 ±5 BC. The function of the trackway and the significance of the Neolithic river crossing at the Kastbjerg Å site are discussed in the light of European parallels and the regional cultural context.